A Review of Recent Studies in Microwave Photonics-based Filter Technologies: MRR-Assisted MZI Case Study - El-edresee, Esraa M.; Al-mfrji, Alhuda A.; Al-Juboori, Haider (Al-Nahrain Journal for Engineering Sciences, 2025)
The recent progress in integrated photonics has promoted microwave photonic filter (MPF) technologies to a supreme level to develop wireless, radar, and internet communication systems. Therefore, the specifications that distinguish the MPF chip include small size, low power, and inexpensive. The MPF that utilized these technologies has demonstrated the merit of wide frequency tuning and reconfiguring by selecting the desired spectral content and rejecting the sideband signals furthermore the immunity to electromagnetic interference. This paper reviews recent techniques involved in microwave filter design on multiple platforms, which involve cascaded micro-ring resonator (MRR), ring-assisted Mach-Zehender-Interferometer (MZI) coupler, Brillion-active waveguide, reflector-type MRR, and Bragg grating with phase shifts. In particular, we demonstrated the output characteristics of the microring integrated with a Mach–Zehnder interferometer coupler technique.